2015
DOI: 10.4172/2329-6895.1000247
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Case of Progressive Multifocal Leukoencephalopathy in a Patient with Non-traditional Risk Factors

Abstract: Case ReportMr. A is a 52 year old man from Qatar with a past medical history of hypertension, diabetes mellitus type 2, hyperlipidemia, diverticulitis status post hemicolectomy, and cervical stenosis of C5-7 who began experiencing intermittent headaches, episodes of slurred speech, and decreased appetite from April to October 2014. In November 2014, he developed progressive weakness of his right lower extremity over three days, to the extent that he was unable to control his right lower extremity or walk prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…While PML without overt immunosuppression has been described in the literature, it is considered an exceedingly rare entity. [3–44] However, our single-center retrospective review suggests that PML without overt immunosuppression may make up a substantial proportion of PML cases (11.8%). Of note, prior population-based studies also reported no obvious immunocompromising disease or treatment in 6.3% [38] and 6.5% [45] of PML patients.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While PML without overt immunosuppression has been described in the literature, it is considered an exceedingly rare entity. [3–44] However, our single-center retrospective review suggests that PML without overt immunosuppression may make up a substantial proportion of PML cases (11.8%). Of note, prior population-based studies also reported no obvious immunocompromising disease or treatment in 6.3% [38] and 6.5% [45] of PML patients.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive literature review of PML in the absence of overt immunosuppression (Table 1) [3–44,46] showed that previously described cases (median age 61 [range 21–81] years; 26% female) were usually found to have underlying comorbidities that may be associated with some degree of immunosuppression, including idiopathic CD4 lymphocytopenia (17/79; 21.5%), chronic renal failure (7/79; 8.9%) [5,22,26] and liver disease (15/70; 19%) most commonly due to hepatitis (6/79; 7.6%) [5,10] or alcoholism (6/79; 7.6%). [5,7,38,43] While case 2 had significant alcohol consumption in the year prior to diagnosis, both laboratory (liver function tests, coagulation studies) and radiographic (computed tomography abdomen) testing did not yield evidence for liver dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations